Konsep estetika bersepadu: terapan dan analisis terhadap karya-karya puisi Ahmad Kamal Abdullah - Abdul Halim Ali (Tanjong Malim, 2010)
Konsep estetika bersepadu: terapan dan analisis terhadap karya-karya puisi Ahmad Kamal Abdullah by Abdul Halim Ali